The Effect of Margin Income and Shares of Results on Net Profit Achieved In BRI Syariah - Astri Anantasari Azizah; Ade Yusuf Mujaddid; Dessy Noor Farida (AL-ARBAH: Journal of Islamic Finance and Banking, 2021)
AbstractPurpose - This study aims to analyze the effect of murabahah margin income, istishna 'margin income, mudharabah profit sharing, and musyarakah revenue sharing on net profit at BRI Syariah Bank during 2014-2019.Method - The research approach used in this research is a quantitative approach. In determining the sample, the research was carried out by using purposive sampling method. In this study, data was collected from secondary data, through quarterly financial reports published by Bank BRI Syariah in 2014-2019. The data analysis technique used is multiple linear regression data analysis techniques, Where researchers can conduct research between two or more independent variables on the dependent variable.Result - The results show that murabahah margin income has a negative and insignificant effect on net profit, istishna 'margin income has a negative and insignificant effect on net income, the profit sharing income from mudharabah has a positive and significant effect on net profit, and the profit sharing income for musyarakah has a negative and negative effect. not significant to net income during 2014-2019.Implication - This study uses BRI Syariah Financial Report data.Originality- This study looks at the relationship between the variable margin income and profit sharing income on the net profit variable generated by Bank BRI Syariah.